Myanmar : Staff Report for the 2014 Article IV Consultation. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2014)
KEY ISSUES Context: The authorities continue to make progress on their far-reaching political and economic reform program. Key economic reform priorities are being realized. However, macroeconomic and financial risks are building, and capacity constraints are slowing institutional reform. Constitutional amendments are being considered ahead of the 2015 elections, and peace negotiations are continuing despite religious and ethnic tensions. Macroeconomic situation and outlook: Growth is accelerating, with average growth projected around 8u percent in the next few years, and inflation should remain broadly stable. After depreciating in 2013, the exchange rate has stabilized. The external current account has widened despite improved export performance but rising capital account inflows should enable Central Bank of Myanmar (CBM)'s international reserves to grow rapidly from their current low levels. Monetary aggregates are growing at double-digit rates. The underlying fiscal deficit in 2013/14 is estimated at 3 percent of GDP and is forecast to widen to around 5 1\2 percent of GDP in 2014/15, but should decline below 5 percent of GDP in the medium term. However, off budget operations could increase the deficit. Risks also arise from capacity constraints and thin fiscal and external buffers. Medium- and long-term prospects: Economic prospects remain strong. Myanmar's long-run growth potential is estimated at around 7 percent, in line with peer countries' experience, but sound institutional and policy frameworks need to be built to realize this. Key policy recommendations: Macroeconomic policy challenges are likely to intensify in the short term. Monetary policy tools need to be more aggressively deployed, and mechanisms established to transfer public sector foreign exchange earnings automatically to the CBM. The regulatory framework for the banking sector needs to be urgently upgraded and supervision strengthened, particularly as foreign banks will soon enter. Tax policy and administration should aim at simplifying the system and preparing for the introduction of a value-added tax (VAT). Technical assistance (TA): Capacity building will be crucial to achieve policy objectives. The IMF continues to provide intensive TA in key areas, including in a wide range of CBM operations, tax policy and administration, public financial management and statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet